Apo A-I binding to platelets detected by flow cytometry - ÖZSAVCI, DERYA (My University, 2001)
Lipoprotein-platelet interactions are very important in atherosclerosis and thrombosis. Several studies have been carried out on specific binding of various lipoproteins to platelets. But there is considerable disagreement about the details of these binding sites. Although low-density lipoprotein (LDL) receptors of several cells have been studied extensively, there is little datum about high-density lipoprotein (HDL) receptors. Apolipoprotein (apo) A-I may play a major role in the determination of the specificity of HDL receptors. In this study, binding of apo A-I to platelets was investigated by using a flow cytometric method. Citrated blood samples were obtained from five healthy and seven hypercholesterolemic subjects. Apo A-I antibody was incubated with the citrated whole blood before and after activation with ADP or thrombin receptor agonist peptide (TRAP). Then fluorescein isothiocyanate (FITC)-labeled secondary antibodies were added and analyzed on a Becton-Dickinson FACSort flow cytometer. In the hypercholesterolemic group, apo A-I binding to platelets was found to be significantly decreased after activation with TRAP (P<.05), but not after activation with ADP. In the control group, after platelet activation with ADP or TRAP, the apo A-I MFI values were not found to be significantly different from the values of resting platelets (P>.05). In this study, we demonstrated that apo A-I can bind to platelets, and this supports the hypothesis that apo A-I may play a major role in HDL binding to platelets.
Keywords: Adult; Female; Humans; Middle Aged; Aged; Adolescent; Male; Flow Cytometry; Protein Binding; Proteins; Risk Factors; Hypercholesterolemia; Arteriosclerosis; Blood Platelets; Adenosine Diphosphate; Lipoproteins, HDL; Platelet Activation; Receptors, Thrombin; Apolipoprotein A-I